Preparation method and application of core-shell structure silicon dioxide blocking agent with rigid inside and soft outside for marine drilling fluid
By polymerizing and grafting specific materials on the surface of nanosilicon dioxide to form a core-shell structure silica sealant with rigid inside and flexible outside, the problems of secondary generation of natural gas hydrates and poor dispersion of nanomaterials in deep-water drilling are solved, efficient sealing and well wall stability are achieved, and drilling safety and efficiency are improved.
Patent Information
- Application Number
- CN202411412444.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In the low temperature and high pressure environment in deep water drilling, the secondary generation of natural gas hydrates leads to the blockage of the wellbore, increasing the risk of equipment failure, and existing nanomaterials are difficult to disperse in the drilling fluid, reducing performance.
Materials such as N-vinyl-2-pyrrolidone, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and dimethyldiallyl ammonium chloride are polymerized and grafted on the surface of nanosilicon dioxide to form a core-shell structure silica sealing agent with rigid inside and flexible outside. With the help of the rigidity of the nanomaterial and the flexibility of polymers, the micro-nano pores of mud shale are efficiently blocked and hydrate formation is inhibited.
Effectively seal the micro-nano pores of deep cement shale formations, maintain the stability of the well wall, inhibit the secondary generation of hydrates, improve the safety and efficiency of deep water drilling, reduce the demand for thermodynamic inhibitors, and have the advantages of environmental protection and cost saving.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a silicon dioxide plugging agent with an inner-rigid and outer-flexible core-shell structure for marine drilling fluid, and belongs to the field of deepwater oil and gas drilling. Background Art
[0002] In recent years, as the exploration and development of onshore oil resources has reached a high level, the newly added reserves and production cannot meet the growing energy demand, and the exploration and development of marine oil and gas resources has attracted much attention. In particular, deep-sea areas have become an important area of global oil exploration. Statistics show that nearly half of the world's major oil and gas discoveries in recent years come from deep-sea areas, showing the importance and potential of deep-sea exploration. The Gulf of Mexico, the Brazilian waters, the West African waters and the South China Sea are currently the most promising deep-water oil and gas areas. Among them, the oil and gas resources in the South China Sea account for one-third of the total national total, and about 70% are distributed in deep waters. These data show that the exploration and development of deep-water marine oil and gas resources is not only the focus of the oil industry, but also the frontier of current scientific research. The deep-water drilling environment is more severe than that of land and shallow-sea drilling, and the technical problems faced are also more complex. These technical problems include wellbore instability, wellbore blockage caused by secondary formation of natural gas hydrates, wellbore collapse, drilling fluid thickening under low temperature conditions, and difficulty in wellbore cleaning. Deepwater formations are usually undercompacted, with poor formation cementation, a large amount of mud shale, and developed micropores and fractures, which makes the drilling process more complicated and difficult. If the drilling fluid has insufficient inhibition, plugging, or filtration and wall-building properties, it will lead to formation instability and frequent well leakage problems. To this end, effective strategies are needed to plug the micro-nano pores in deep cement shale formations and select plugging materials with appropriate particle sizes to ensure wellbore stability.
[0003] At present, the application of nanotechnology in the field of drilling has promoted the rapid development of the oil exploration industry. Nanomaterials can seal the microcracks and micropores of shale, thereby reducing permeability and pressure transmission, enhancing the bearing capacity of the formation, and improving the stability of the wellbore. The application of nanoparticles in drilling fluid can not only reduce damage to the formation, but also enhance the rheological properties and maintain the stability of the wellbore. However, the silanol groups on the surface of nanoparticles are easy to polymerize, making them difficult to disperse in the drilling fluid, thereby reducing the overall performance. In order to solve this problem, the dispersibility of nanoparticles in drilling fluid can be significantly improved through chemical modification.
[0004] During deepwater drilling, the seabed temperature is often very low, sometimes even dropping below 0°C. At the same time, the hydrostatic pressure in the deepwater environment is extremely high, reaching more than 30MPa. This low-temperature and high-pressure environment can easily lead to the secondary generation of natural gas hydrates in the drilling fluid. The generated hydrates will block key equipment such as pipelines and blowout preventers, which will have a serious impact on drilling operations. The blockage of hydrates will not only interrupt drilling operations, but also increase the risk of equipment failure and may even cause safety accidents, posing a major threat to the entire drilling process. Therefore, the secondary generation of natural gas hydrates in the low-temperature and high-pressure environment in deepwater drilling is an urgent problem to be solved. In order to deal with these problems, a plugging agent suitable for low-temperature and high-pressure environments that can block micro-nano pores and inhibit hydrate formation is needed. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a preparation method and application of a core-shell structured silica plugging agent for marine drilling fluid.
[0006] The present invention adopts N-vinyl-2-pyrrolidone, dimethyldiallylammonium chloride, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid to polymerize and graft on the surface of nano-silica to form a core-shell structured silica plugging agent which is hard inside and soft outside. With the help of the rigid plugging of nano-materials and the flexible plugging of deformation filling of high molecular polymers, the micro-nano pores of mudstone are efficiently blocked with hard inside and soft outside, thereby maintaining the stability of the well wall, and effectively inhibiting the secondary generation of hydrates, thereby improving the safety and efficiency of deep-water drilling. In addition, the plugging agent of the present invention reduces the demand for a large amount of thermodynamic inhibitors, which not only saves costs but also has environmental protection characteristics.
[0007] The technical solution of the present invention is as follows: A method for preparing a core-shell structured silica plugging agent for marine drilling fluid, comprising the following steps: The acrylamide aqueous solution, the 2-acrylamido-2-methylpropanesulfonic acid aqueous solution, the dimethyldiallylammonium chloride aqueous solution, the N-vinyl-2-pyrrolidone and the KH570 modified nano-silica aqueous solution are uniformly mixed; the pH value is adjusted, and the initiator aqueous solution is added dropwise under a protective atmosphere and stirring conditions; the reaction is stirred under a protective atmosphere, and then washed, dried and crushed to obtain an inner-rigid and outer-flexible core-shell structure silica plugging agent for marine drilling fluid.
[0008] Preferably according to the present invention, the mass concentration of the acrylamide aqueous solution is 7-13wt%.
[0009] Preferably, according to the present invention, the mass concentration of the 2-acrylamido-2-methylpropanesulfonic acid aqueous solution is 19-21wt%.
[0010] Preferably according to the present invention, the mass concentration of the dimethyldiallylammonium chloride aqueous solution is 60wt%.
[0011] Preferably according to the present invention, the mass concentration of the KH570 modified nano-silicon dioxide aqueous solution is 4-8wt%.
[0012] Preferably according to the present invention, the particle size of KH570 modified nano-silicon dioxide is 10-20 nm.
[0013] Preferably according to the present invention, the molar ratio of N-vinyl-2-pyrrolidone, dimethyldiallylammonium chloride, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is (3-1): (2-1): (4-2): (3-6).
[0014] Preferably according to the present invention, the mass ratio of N-vinyl-2-pyrrolidone to KH570 modified nano-silica is (1-5): (2-6).
[0015] Preferably, according to the present invention, the mixing is carried out under stirring conditions, the stirring rate is 200-400 rpm, the stirring time is 15-30 minutes, and the mixing temperature is 20-30°C.
[0016] According to the present invention, preferably, the protective atmosphere is nitrogen or argon.
[0017] According to the present invention, preferably, the pH is adjusted to 7.
[0018] Preferably, according to the present invention, the mass concentration of the initiator aqueous solution is 2%-15%; the initiator is a redox composite initiator of ammonium persulfate and sodium bisulfite, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 1:1.
[0019] Preferably according to the present invention, the mass of the initiator is 0.1%-1% of the total mass of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dimethyldiallylammonium chloride, N-vinyl-2-pyrrolidone and KH570 modified nano-silica.
[0020] Further preferably, the mass of the initiator is 0.1%-0.5% of the total mass of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dimethyldiallylammonium chloride, N-vinyl-2-pyrrolidone and KH570 modified nano-silica.
[0021] According to the preferred embodiment of the present invention, the dripping rate of the initiator aqueous solution is one drop every 2-4 seconds.
[0022] Preferably according to the present invention, after the initiator is added dropwise, the stirring reaction temperature is 55-85° C., the stirring speed is 100-400 rpm, and the stirring reaction time is 6 h.
[0023] Preferably, according to the present invention, washing is performed using a mixed solution of anhydrous ethanol and acetone; and the drying temperature is 55-85°C.
[0024] The present invention adopts N-vinyl-2-pyrrolidone, dimethyldiallylammonium chloride, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid to polymerize and graft on the surface of nano-silicon dioxide to form a core-shell structured silicon dioxide plugging agent which is hard inside and soft outside. The microscopic morphology is a core-shell structure, with modified nano-silicon dioxide (SiO2) as the core and a polymer shell layer coated on the outside.
[0025] A core-shell structured silica plugging agent with hard inner side and soft outer side for marine drilling fluid is prepared by the above method.
[0026] The above-mentioned core-shell structured silica plugging agent for marine drilling fluid is used as a micro-nano plugging agent in deep-water drilling to plug the micro-nano pores in the formation and inhibit the secondary generation of natural gas hydrates in the wellbore.
[0027] The technical features and beneficial effects of the present invention are as follows: 1. The present invention polymerizes N-vinyl-2-pyrrolidone, dimethyldiallylammonium chloride, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid and grafts them on the surface of nano-silica to form a core-shell structured silica plugging agent that is rigid inside and flexible outside. With the help of the rigid plugging of nano-materials and the flexible plugging of deformation filling of high molecular polymers, the micro-nano pores of shale are efficiently blocked by the rigid plugging of nano-materials and the flexible plugging of deformation filling of high molecular polymers, thereby maintaining the stability of the well wall, effectively inhibiting the secondary generation of hydrates, and improving the safety and efficiency of deep-water drilling. In addition, the plugging agent of the present invention reduces the demand for a large amount of thermodynamic inhibitors, which not only saves costs, but also has environmental protection characteristics; the preparation method is simple, the raw materials are cheap and easy to obtain, and the plugging agent is efficient and environmentally friendly; and the plugging agent has good compatibility with the drilling fluid.
[0028] 2. The molecular chain of acrylamide can flexibly fill and adapt to the different shapes and sizes of microcracks or pores, providing flexible enhanced sealing effect. The amide group will be adsorbed at different positions in the clay, and the resulting more adsorption points will prevent the invasion of water phase on the clay surface, and desorption is not easy to occur, and it will inhibit the hydration of clay for a long time. The amide group of acrylamide can form a strong adsorption layer on the surface of shale and natural gas hydrate crystals, inhibiting the expansion and dispersion of clay minerals and the decomposition of hydrates; 2-acrylamide-2-methylpropanesulfonic acid (AMPS) can enhance the temperature and salt resistance of polymers. At the same time, AMPS contains sulfonic acid groups and hydroxyl groups, which increase the thermal stability of the polymer. Stronger bonding CS and CN bonds also improve temperature resistance; the cations of dimethyldiallylammonium chloride (DMDAAC) will be adsorbed on the clay surface through electrostatic action, and a part of them will enter the interlayer and replace the interlayer cations, thereby expelling the interlayer water molecules. The positive charge provided by DMDAAC can form a strong charge adsorption with the negatively charged clay minerals in the shale, enhancing the polymer The invention discloses a novel nano-silica plugging agent, which has a good plugging property and inhibitory effect on the surface of the composite; N-vinyl-2-pyrrolidone is a polymer monomer of the kinetic hydrate inhibitor PVP. The introduction of N-vinyl-2-pyrrolidone, on the one hand, inhibits the secondary formation of hydrates, and on the other hand, makes the polymer shell layer coated on the outside of the silica have better flexibility; the specific acrylamide aqueous solution, 2-acrylamido-2-methylpropanesulfonic acid aqueous solution, dimethyldiallylammonium chloride aqueous solution, N-vinyl-2-pyrrolidone and KH570 modified nano-silica ratio of the invention makes the obtained plugging agent have a complete shell layer and make the polymer shell layer have better flexibility, forming a core-shell structure silica plugging agent with inner rigidity and outer softness, and having stronger micron-level plugging ability.
[0029] 3. Experiments have shown that after adding the plugging agent of the present invention at a mass fraction of 1% to a 4% freshwater base slurry, the API filtration loss of the base slurry is reduced from 22 mL to 10 mL, and the high-temperature and high-pressure filtration loss after aging at 180°C is reduced from 90 mL to 58 mL, the apparent viscosity is increased from 10 mPa·s to 32.5 mPa·s, the plastic viscosity is increased from 6 mPa·s to 19 mPa·s, and the dynamic shear force is increased from 4 Pa to 13.5 Pa, indicating that the present invention has good filtration loss reduction properties at both room temperature and high temperature and high pressure, and can play a role in viscosity increase and shear improvement, optimize the rheological properties of the base slurry, and can also indirectly indicate that it has an excellent plugging effect. Testing the 160-180 mesh medium-pressure sand bed plugging experiment and microporous filter membrane experiment of the present invention both show that the present invention has good micro-nano pore plugging ability. The hydrate secondary formation inhibition performance evaluation experiment shows that the present invention also has a certain hydrate formation inhibition performance, reducing the need for a large amount of thermodynamic inhibitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1This is a SEM picture of the microporous filter membrane after being blocked by the micro-nano blocking agent prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0032] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and equipment described are all commercially available unless otherwise specified.
[0033] Example 1 A method for preparing a core-shell structured silica plugging agent for marine drilling fluid, wherein the plugging agent is suitable for deepwater drilling fluid, comprises the following steps: (1) 3 g of KH570 modified nano-silica was uniformly mixed with 50 g of pure water at 25° C. and stirred for 20 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano-silica aqueous solution; (2) 6.3 g (0.089 mol) of acrylamide and 60 g of pure water were uniformly mixed at 25°C, and stirred for 10 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution; (3) adding 11.02 g (0.053 mol) of 2-acrylamide-2-methylpropanesulfonic acid to the aqueous acrylamide solution obtained in step (2), stirring for 10 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed aqueous solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid; (4) adding an aqueous solution of 9.56 g (0.035 mol) of dimethyldiallylammonium chloride (60 wt%), 3.94 g (0.035 mol) of N-vinyl-2-pyrrolidone and the KH570 modified nano-silica aqueous solution obtained in step (1) to the mixed aqueous solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid obtained in step (3) to obtain a mixed solution; (5) The mixed solution was adjusted to pH 7 using 20% NaOH solution and placed in a constant temperature water bath. Nitrogen was continuously introduced for 30 minutes at 65°C and 300 rpm to expel the air in the flask while continuing to stir. (6) Weigh 0.045 g of ammonium persulfate and 0.045 g of sodium bisulfite, dissolve them in 10 mL of pure water, and obtain 10 mL of ammonium persulfate and sodium bisulfite redox composite initiator aqueous solution; under stirring and nitrogen protection, add the initiator aqueous solution to the system of step (5) at a rate of 2 drops per second; after the addition is completed, continue to react for 6 hours at a stirring rate of 300 rpm, a temperature of 65°C, and nitrogen conditions; after the reaction is completed, wash with a mixed solution of anhydrous ethanol and acetone, dry in a vacuum drying oven at 70°C for 24 hours, and crush to obtain a core-shell structured silica plugging agent with an inner rigidity and an outer softness.
[0034] Example 2 A method for preparing a core-shell structured silica plugging agent for marine drilling fluid, wherein the plugging agent is suitable for deepwater drilling fluid, comprises the following steps: (1) 3 g of KH570 modified nano-silica was uniformly mixed with 50 g of pure water at 25°C, and stirred for 20 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano-silica aqueous solution.
[0035] (2) 6.39 g (0.090 mol) of acrylamide and 60 g of pure water were uniformly mixed at 25°C and stirred for 10 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution.
[0036] (3) 12.43 g (0.060 mol) of 2-acrylamide-2-methylpropanesulfonic acid was added to the aqueous acrylamide solution obtained in step (2), and the mixture was stirred for 10 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed aqueous solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid.
[0037] (4) An aqueous solution containing 9.56 g (0.030 mol) of dimethyldiallylammonium chloride (60 wt%), 3.94 g (0.030 mol) of N-vinyl-2-pyrrolidone and the KH570 modified nano-silica aqueous solution obtained in step (1) was added to the mixed aqueous solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid obtained in step (3) to obtain a mixed solution.
[0038] (5) The mixed solution was adjusted to pH 7 using 20% NaOH solution and placed in a constant temperature water bath. Nitrogen was continuously introduced for 30 minutes at 65°C and 300 rpm to expel the air in the flask while continuing to stir. (6) Weigh 0.045g of ammonium persulfate and 0.045g of sodium bisulfite and dissolve them in 10mL of pure water to obtain 10mL of ammonium persulfate and sodium bisulfite redox composite initiator aqueous solution. Under stirring conditions and nitrogen protection, add the initiator aqueous solution to the system in step (5) at a rate of 2 drops per second; after the addition is completed, continue to react for 6 hours at a stirring rate of 300rpm, a temperature of 65°C and nitrogen conditions; after the reaction is completed, wash with a mixed solution of anhydrous ethanol and acetone, dry in a vacuum drying oven at 70°C for 24h, and crush to obtain a core-shell structured silica plugging agent with an inner rigidity and an outer softness.
[0039] Example 3 A method for preparing a core-shell structured silica plugging agent for marine drilling fluid, wherein the plugging agent is suitable for deepwater drilling fluid, comprises the following steps: (1) 3 g of KH570 modified nano-silica was uniformly mixed with 50 g of pure water at 25°C, and stirred for 20 minutes at a stirring rate of 200 r / min to obtain a KH570 modified nano-silica aqueous solution.
[0040] (2) 6.3 g (0.089 mol) of acrylamide and 60 g of pure water were uniformly mixed at 25°C and stirred for 10 minutes at a stirring rate of 200 r / min to obtain an acrylamide aqueous solution.
[0041] (3) 11.02 g (0.053 mol) of 2-acrylamide-2-methylpropanesulfonic acid was added to the aqueous acrylamide solution obtained in step (2), and the mixture was stirred for 10 minutes at a stirring rate of 200 r / min and a temperature of 25° C. to obtain a mixed aqueous solution of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid.
[0042] (4) An aqueous solution containing 9.56 g (0.035 mol) of dimethyldiallylammonium chloride (60 wt%), 3.94 g (0.035 mol) of N-vinyl-2-pyrrolidone and the KH570 modified nano-silica aqueous solution obtained in step (1) was added to the mixed aqueous solution of acrylamide and 2-acrylamido-2-methylpropanesulfonic acid obtained in step (3) to obtain a mixed solution.
[0043] (5) The mixed solution was adjusted to pH 7 using 20% NaOH solution and placed in a constant temperature water bath. Nitrogen was continuously introduced for 30 minutes at 65°C and 300 rpm to expel the air in the flask while continuing to stir. (6) Weigh 0.015g of ammonium persulfate and 0.015g of sodium bisulfite and dissolve them in 10mL of pure water to obtain 10mL of ammonium persulfate and sodium bisulfite redox composite initiator aqueous solution. Under stirring conditions and nitrogen protection, add the initiator aqueous solution to the system in step (5) at a rate of 2 drops per second; after the addition is completed, continue to react for 6 hours at a stirring rate of 300rpm, a temperature of 80°C and nitrogen conditions; after the reaction is completed, wash with a mixed solution of anhydrous ethanol and acetone, dry in a vacuum drying oven at 70°C for 24h, and crush to obtain a core-shell structured silica plugging agent with an inner rigidity and an outer softness.
[0044] Comparative Example 1 A method for preparing a micro-nano plugging agent is carried out according to the preparation method of Example 1, except that the amount of 2-acrylamide-2-methylpropanesulfonic acid used is 6 g (0.029 mol), and the other steps and conditions are consistent with Example 1.
[0045] Comparative Example 2 A method for preparing a micro-nano plugging agent is carried out according to the preparation method of Example 1, except that the amount of N-vinyl-2-pyrrolidone used is 1.12 g (0.010 mol), and the other steps and conditions are consistent with Example 1.
[0046] Comparative Example 3 A method for preparing a micro-nano plugging agent is carried out according to the preparation method of Example 1, except that the amount of N-vinyl-2-pyrrolidone used is 7.84 g, and the other steps and conditions are consistent with Example 1.
[0047] Comparative Example 4 A method for preparing a micro-nano plugging agent is carried out according to the preparation method of Example 1, except that the amount of acrylamide used is 1.2 g, and the other steps and conditions are consistent with Example 1.
[0048] Comparative Example 5 A method for preparing a micro-nano plugging agent is carried out according to the preparation method of Example 1, except that the amount of KH570 modified nano-silicon dioxide used is 0.5 g, and the other steps and conditions are consistent with Example 1.
[0049] Comparative Example 6 A method for preparing a micro-nano plugging agent is as described in Example 1, except that the mass fraction of the initiator is 1%, and the other steps and conditions are consistent with those in Example 1.
[0050] Test Example 1 With reference to the national standard "GB / T 29170-2012 Laboratory Test of Drilling Fluids in the Petroleum and Natural Gas Industry", the rheological parameters of the base slurry of the examples or comparative examples, as well as the filtration loss at room temperature and pressure and the filtration loss at high temperature and high pressure after aging were measured. The experimental results are shown in Table 1.
[0051] Table 1 Rheological filtration test of the base slurry with the samples of the examples and comparative examples It can be seen from the results in Table 1 that the plugging agents prepared by Examples 1-3 of the present invention have little effect on the rheological properties of the base slurry before and after aging at 180°C for 16 hours, and effectively reduce the high-temperature and high-pressure filtration loss of the base slurry; before hot rolling, the filtration loss is 10-3mL, and after aging at 180°C for 16 hours, the filtration loss is controlled at 40-52mL, indicating that the plugging agent of the present invention has good temperature resistance; while the amount of 2-acrylamido-2-methylpropanesulfonic acid used in Comparative 1 is too small, and the monomer accounts for a small proportion, resulting in insufficient temperature resistance of the product, so the plugging effect is not ideal. In Comparative Example 2, the amount of N-vinyl-2-pyrrolidone used is too little, resulting in an incomplete product shell layer, so the plugging effect is poor. In Comparative Example 3, the amount of N-vinyl-2-pyrrolidone used is too much, resulting in low flexibility of the product shell layer and poor plugging effect. In Comparative Example 4, the amount of acrylamide used is too little, resulting in an incomplete product shell layer, few sites, and poor plugging effect. In Comparative Example 5, the amount of KH570 modified nano-silica used is too little, the plugging agent has insufficient rigidity and is easy to collapse, resulting in poor plugging effect. In Comparative Example 6, due to the high mass fraction of the initiator, the reaction is too violent, the monomer self-polymerization phenomenon is serious, and the conversion rate is low, so the plugging effect is not ideal.
[0052] Test Example 2 The 160-180 mesh sand was used to simulate the micron-scale pore development formation and the plugging performance of the sample was tested. Figure 1 , as shown in Table 2.
[0053] Table 2 Medium pressure sand bed plugging experiment It can be seen from Table 2 that all the base slurry after hot rolling is lost, while the penetration depth of the base slurry after hot rolling + 1% Example 1 in the sand bed is 4 cm, and the penetration depth of the base slurry + 1% Comparative Example 1 in the sand bed is 10.2 cm, which shows that compared with Comparative Example 1, Example 1 of the present invention has stronger micron-level plugging ability.
[0054] Test Example 3 A microporous filter membrane was used to simulate the nano-scale pore development environment of deepwater shale. The filtration loss of samples was measured at room temperature and pressure using microporous filter membranes with different pore sizes. The results are shown in Table 3.
[0055] Table 3 Microporous membrane filtration test It can be seen from Table 3 that, compared with pure water and comparative example 4, example 1 can more effectively block nanoscale pores of different sizes, thereby significantly reducing the filtration loss of the microporous membrane, indicating that example 1 of the present invention has good nanoscale blocking ability.
[0056] Test Example 4 The sample was subjected to an experiment to evaluate the performance of inhibiting the secondary formation of hydrates. The gas pipeline and the methane cylinder were opened, and the pressure was increased to 20 MPa using a gas booster. A 1 wt% aqueous solution of the inhibitor was prepared and placed in a reactor. After the reactor was evacuated, methane gas was introduced to generate hydrates in an environment of 14 MPa and 0 °C. A data acquisition system was used to record data including liquid measurement temperature, gas measurement temperature, pressure, stirring torque, etc. in real time. When the pressure change in the reactor was less than or equal to 0.01 MPa in half an hour, the hydrate formation was considered complete. The experimental results are shown in Table 4.
[0057] Table 4 Hydrate formation inhibition test As can be seen from Table 4, compared with pure water and Comparative Example 3, adding 1% of Example 1 can extend the time for large-scale hydrate formation to 6.95 h, and reduce the large-scale formation temperature from 9.56°C to 3.24°C, which illustrates the importance of the proportion of kinetic hydrate inhibition monomers, and also shows that Example 1 has good hydrate secondary formation inhibition performance.
Claims
1. A method for preparing a core-shell structured silica plugging agent for marine drilling fluid, characterized in that: The steps include: The acrylamide aqueous solution, the 2-acrylamido-2-methylpropanesulfonic acid aqueous solution, the dimethyldiallylammonium chloride aqueous solution, the N-vinyl-2-pyrrolidone and the KH570 modified nano-silica aqueous solution are uniformly mixed; the pH value is adjusted, and the initiator aqueous solution is added dropwise under a protective atmosphere and stirring conditions; the reaction is stirred under a protective atmosphere, and then washed, dried and crushed to obtain an inner-rigid and outer-flexible core-shell structure silica plugging agent for marine drilling fluid.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the acrylamide aqueous solution is 7-13wt%, the mass concentration of the 2-acrylamido-2-methylpropanesulfonic acid aqueous solution is 19-21wt%, the mass concentration of the dimethyldiallylammonium chloride aqueous solution is 60wt%, the mass concentration of the KH570 modified nano-silica aqueous solution is 4-8wt%, and the particle size of the KH570 modified nano-silica is 10-20nm.
3. The preparation method according to claim 1, characterized in that: The molar ratio of N-vinyl-2-pyrrolidone, dimethyldiallylammonium chloride, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is (3~1):(2~1):(4~2):(3~6).
4. The preparation method according to claim 1, characterized in that: The mass ratio of N-vinyl-2-pyrrolidone to KH570 modified nano-silica is (1-5): (2-6).
5. The preparation method according to claim 1, characterized in that: The mixing is carried out under stirring conditions, with a stirring rate of 200-400 rpm, a stirring time of 15-30 minutes, a mixing temperature of 20-30° C., a protective atmosphere of nitrogen or argon, and a pH value adjusted to 7.
6. The preparation method according to claim 1, characterized in that: The mass concentration of the initiator aqueous solution is 2%-15%; the initiator is a redox composite initiator of ammonium persulfate and sodium bisulfite, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 1:1, and the mass of the initiator is 0.1%-1% of the total mass of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dimethyldiallylammonium chloride, N-vinyl-2-pyrrolidone and KH570 modified nano-silica.
7. The preparation method according to claim 1, characterized in that: The dropping rate of the initiator aqueous solution is one drop every 2-4 seconds. After the initiator is added, the stirring reaction temperature is 55-85°C, the stirring speed is 100-400 rpm, and the stirring reaction time is 6 hours.
8. The preparation method according to claim 1, characterized in that: The washing is performed using a mixed solution of anhydrous ethanol and acetone; the drying temperature is 55-85°C.
9. A core-shell structured silica plugging agent for marine drilling fluid, prepared by the method according to any one of claims 1 to 8.
10. Use of the inner-rigid and outer-flexible core-shell silica plugging agent for marine drilling fluid as claimed in claim 9 as a micro-nano plugging agent in deep-water drilling to plug micro-nano pores in the formation and inhibit the secondary generation of natural gas hydrates in the wellbore.
Citation Information
Patent Citations
Polymer microsphere as well as preparation method and application thereof
CN113881000A
Flexible-outside rigid-inside multi-walled carbon nanotube nano plugging agent and oil-based drilling fluid
CN114214047A
Multifunctional treating agent for natural gas hydrate drilling fluid in sea area as well as preparation method and application of multifunctional treating agent
CN114874391A
High-temperature-resistant and high-salt-resistant filtrate reducer for drilling fluid and preparation method of filtrate reducer
CN116410422A
Temperature-resistant and salt-resistant zwitterionic nano blocking agent as well as preparation and application thereof
CN116444743A
Cited By
Nano blocking agent for drilling fluid and preparation method thereof
CN120988215A
A nano plugging agent for drilling fluid and a preparation method thereof
CN120988215B
Free radical polymerization water-based drilling fluid composition and preparation method thereof
CN121652775A
Broad-spectrum anti-pollution spacer fluid for ultra-deep well cementation and preparation method of broad-spectrum anti-pollution spacer fluid
CN122302849A
Broad-spectrum anti-pollution spacer fluid for cementing ultra-deep wells and preparation method thereof
CN122302849B